Solar Tracking System with Photovoltaic Cells: Experimental Analysis at High Altitudes - Elmer Rodrigo Aquino Larico; Angel Canales Gutierrez (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
There is currently an urgent need to study the application of solar energy to photovoltaic systems due to the need to produce electricity; indeed, maximizing the performance of solar energy promotes efficient and sustainable energy systems. The objective of this study was to determine the photovoltaic performance of a dual-axis solar tracker based on photovoltaic cells with different inclination angles at high altitudes above 3800 m.a.s.l. A solar tracking system activated by two linear actuators was implemented to automatically follow the trajectory of the sun during the day, and the results were compared with those from a fixed photovoltaic system. In addition, due to the climatic variation in the area, photovoltaic cells installed at different inclination angles were used to maximize electricity production and processed by a programmable logic controller (PLC). Finally, principal component analysis (PCA) was used to determine the factors that influenced the performance of the photovoltaic system during the experimental period. The results showed that the maximum monthly performance of the solar tracker was 37.63% greater than that of the fixed system, reaching 10.66 kWh/m2/d on sunny days in peak sun hours (PSH). On days with frequent rain and clouds, the partial yield was less than 14.38%, with energy production during PSH of 6.54 kWh/m2/d. Therefore, in this high-altitude area, the performance of the solar tracker was greater from July to October; from November to February, the performance was reduced due to the occurrence of rain.